Kode Sastra dalam Sastra Lisan Aceh Hikayat Jugi Tapa - Yulsafli Yulsafli; Burhanuddin AG; Ismawirna Ismawirna (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
Jugi Tapa saga is oral literature in Sawang District. North Aceh Regency, Aceh Province. This saga tells the story of the main character named Leubee Muda. Then, Leubee Muda became a heretic because he opposed his teacher named Teungku Lhok Drien. After his heresy, he was called Jugi Tapa, who became the title of this saga.One day, his teacher asked him to deliver a book to Teungku Jambo Haji. The teacher advised him not to read the book. However, Leubee Muda violated the mandate of his teacher, he read and practiced the entire contents of the book. Because of his intelligence, in a short time, he can master all the knowledge contained in the book.To perfect his magic, he must meditate and marry one hundred beautiful women, some of whom are king's wives and daughters of dignitaries. Jugi Tapa had married eighty-eight beautiful women. Amat Banta's mother, King Sadon's wife from Kuala Diwa, was his 99th wife. He needs one more woman as his hundredth wife as a condition of perfecting his power. Before obtaining a hundred women, he could not have sex with a woman, and he continued to meditate in the palace which he made with magic.His 99th wife was Putro Bunsu, the wife of King Sadon of the Kingdom of Kuala Diwa, having a son named Amat Banta. When Jugi Tapa brought his mother, Amat Banta was three days old. The Mother left a ring in the swing of her little son. Later that ring was the proof that he was her son she had left behind.Based on information from Bing Pho in Indonesian called Kepiting Uca (fiddler crab), Amat Banta looked for his mother to Blang Laka (in the current known as Bener Meriah Regency), where Jugi Tapa collected ninety-nine women, including Amat Banta's mother. With the help of Amat Banta ’s mother who had obtained the secret of Jugi Tapa's magic from Jugi Tapa's mouth, Amat Banta managed to kill Jugi Tapa.Several messages can be taken from the story of Jugi Tapa, both as symbols, indexes, and icons. First, good deeds do not always get good replies. Therefore, every good work must be done sincerely so that we are not disappointed later on. Second, women should not be kept secret. Third, we cannot fight the teacher.